Interruption in Interaction of Research Presentation - Ferawaty Syam (State Islamic Institute of Bone, Indonesia, 2021)
The present study highlights the communication which is concerned spoken discourse that occurs in an interaction in research presentations. The goals of this study are to explore how the interruptions in interaction are used in EFL (English a Foreign Language) students’ research presentation and what sorts and intentions on it. Thus, this study scrutinizes EFL students who presented research proposals and lecturers who supervised and examined them at the postgraduate program of State University of Makassar in 2017. The number of participants in this study was 20 academicians who were taken as a sample purposively. This study was navigated by descriptive qualitative method. To collect data, the writer employed discourse analysis approach by using video recorder to probe the spoken of speaker in doing conversation. Data recording was transformed into transcript. The transcription was coded to obtain the excerpt to be interpreted to find out the sorts of interruption in interaction of research presentation. Findings exposed that interruption are delivered in a competitive and cooperative manner. The two forms of interruption, there are two sorts with several intentions, including alert that aims to remind, inform, and correct the previous speaker. In addition, there is also a met comment that aims to questioning, suggesting, and jesting.